2019
DOI: 10.1371/journal.pone.0221431
|View full text |Cite
|
Sign up to set email alerts
|

Flagella-dependent inhibition of biofilm formation by sub-inhibitory concentration of polymyxin B in Vibrio cholerae

Abstract: Biofilm formation is a common strategy used by bacteria in order to survive and persist in the environment. In Vibrio cholerae ( V . cholerae ), a Gram-negative pathogen responsible for the cholera disease, biofilm-like aggregates are important for the pathogenesis and disease transmission. Biofilm formation is initiated by the attachment of the bacteria to a surface, followed by maturation stages involving the formation of a biofilm matrix. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 77 publications
(88 reference statements)
7
42
1
1
Order By: Relevance
“…This inhibition occurred during the early stage of biofilm formation and was correlated with a reduction in the number of flagellated bacteria. Therefore, besides biofilm formation, V. cholerae motility was also impaired in the presence of PmB [66]. A similar effect of indolicin has been reported on P. aeruginosa motility and biofilm formation and involves PsrA, a positive regulator of the type III secretion system important for virulence [67,68].…”
Section: Modulation Of Biofilm Formationsupporting
confidence: 67%
See 1 more Smart Citation
“…This inhibition occurred during the early stage of biofilm formation and was correlated with a reduction in the number of flagellated bacteria. Therefore, besides biofilm formation, V. cholerae motility was also impaired in the presence of PmB [66]. A similar effect of indolicin has been reported on P. aeruginosa motility and biofilm formation and involves PsrA, a positive regulator of the type III secretion system important for virulence [67,68].…”
Section: Modulation Of Biofilm Formationsupporting
confidence: 67%
“…This reduction is accentuated by the combination of polymyxin B with gramicin S, another AMP. We recently demonstrated that a subinhibitory concentration of PmB can inhibit biofilm formation in V. cholerae [66]. This inhibition occurred during the early stage of biofilm formation and was correlated with a reduction in the number of flagellated bacteria.…”
Section: Modulation Of Biofilm Formationmentioning
confidence: 96%
“…Some of these genes are directly involved in biofilm formation. For instance, flagella are known to be essential for cell adhesion in the early stages of biofilm formation [ 169 ]. Then, the upregulation of flagellar structures could induce the formation of robust biofilms, representing a protective strategy against HOCl stress.…”
Section: Adaptive Response Of Gram-negative Cells To Hoclmentioning
confidence: 99%
“…Several bacteria, such as B. cereus and E. coli O157:H7, also form multispecies biofilms to enhance their survival in food-processing lines [ 94 , 95 ]. The formation of biofilms is also dependent on bacterial structures that are responsible for initial surface attachment, such as flagella and/or fimbriae (for example, curli) in L. monocytogenes [ 96 , 97 ], S. Typhimurium [ 98 , 99 ], E. coli O157:H7 [ 100 ] and V. cholerae [ 101 ].…”
Section: Pathogenic Bacteria In Foodmentioning
confidence: 99%